PRIORITAS STRATEGI PENGHAPUSAN BENTUK-BENTUK PEKERJAAN TERBURUK UNTUK ANAK DI PROVINSI LAMPUNG DALAM PERSPEKTIF TIME MATRIX MANAGEMENT - Mukhlis, Maulana (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
One focus of the twelve categories of children who need attention to be protected is child labor in its various forms. Child labor (according to Law No. 1 of 2000 on the ratification of ILO Convention No. 182 concerning the prohibition and immediate action for the elimination of the worst forms of child) includes children who are physically and economically. Lampung Province has 165 402 child labor (child labor instead of child work) in the 5-17 year age category. The amount is greatly influenced by factors of poverty. The purpose of this study is to provide recommendations (suggestions) policies and strategies for the elimination of the worst forms of child in Lampung province so that the entire classification (forms of) child labor as stipulated in Law No. 1 Year 2000 can be accommodated. By using a rational approach comprehensively in the stages of policy formulation, the results showed that although had been many efforts in the province of Lampung (institutional aspects and programs), but there are still problems in the similarity measures and actions among stakeholders in the handling of child labor and have not effective institutions that have been established. Also a weakness in this aspect of policy substance. Therefore, the policy recommended is (a) data collection and mapping by name by address, (b) campaigns and dissemination of information, (c) assessment and development model of the elimination of the worst forms of child labor, (d) harmonization of the rules of the area, (e ) strengthening institutional capacity, (f) the handling of integration and cooperation, (g) the guidance and protection by sector, namely in the field of education, health, employment, social, cultural, and economic.